Pythagorean Theorem<h2>
Verbally:</h2>
Let's say a and b are the legs, and c is the hypotenuse. Then, algebraically, the theorem is,
Hello! :)
To solve your equation, we will first simplify both sides of the equation
-7 = -1 + x/3
-7 = -1 + 1/3x
-7 = 1/3x - 1
Next, we will flip the equation
1/3x - 1 = -7
Third, we will add 1 to both sides
1/3x - 1 + 1 = -7 + 1
1/3x = -6
Last, we will Multiply both sides by 3
3 * (1/3x) = (3) * (-6)
x = -18 (ANSWER)
That means -18 is you answer
Hope this helped you!
THEDIPER
Answer: I added an attachment of what the graph should look like! :)
Step-by-step explanation:
1/y = -3x /2 + 3
mulytiply each term by 2y:-
2 = -3xy + 6y
y = 2 / -3( (x - 2)
y = -0.667 (-2 + x)